Managing Eco-Theological Integration in Polytechnic Islamic Religious Education: Pedagogical Practices and Institutionalization Gaps - Waway Qodratulloh S; Sumiyati; Satria Kharimul Qolbi; Mochammad Arif Budiman; Suherman; Neneng Nuryati; Muhamad Arif Nugraha (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
This study examines how Islamic eco-theological values are articulated, enacted, experienced, and institutionally supported within Islamic Religious Education (PAI) learning in Indonesian polytechnics. Using an exploratory, qualitative, multisite design, the study was conducted at three state polytechnics through semi-structured interviews with nine PAI lecturers and 15 students who had completed PAI courses, non-participant observations of classroom and off-class learning activities, and analysis of semester learning plans, instructional materials, and assessment instruments. Data were analyzed thematically through a hybrid deductive–inductive approach, followed by within-site and cross-site comparison. The findings show that concepts such as khalifah, amanah, mizan, and the prohibition of fasad provided a shared normative foundation across the three institutions, but their pedagogical enactment varied. Conceptual transmission corresponded mainly with affective and reflective responses, habit-oriented learning with observable everyday practices, and contextual-experiential learning with more dialogical and participatory engagement. These patterns do not establish a causal sequence. Across all sites, ecological integration remained weakly embedded in learning outcomes, instructional guidance, assessment, and institutional policy, leaving implementation dependent on individual lecturers. The study positions Eco-Theo-Pedagogy as an analytical framework linking theological meaning, pedagogical practice, student engagement, vocational relevance, and institutional support. It identifies preliminary requirements for future development, including curricular articulation, contextual and experiential learning, vocational relevance, ecological action, assessment alignment, and lecturer and institutional support.